2023
DOI: 10.1186/s13578-023-00981-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptionally imprinted glycomic signatures of acute myeloid leukemia

Abstract: Background Acute myeloid leukemia (AML) is a genetically and phenotypically heterogeneous disease that has been suffering from stagnant survival curves for decades. In the endeavor toward improved diagnosis and treatment, cellular glycosylation has emerged as an interesting focus area in AML. While mechanistic insights are still limited, aberrant glycosylation may affect intracellular signaling pathways of AML blasts, their interactions within the microenvironment, and even promote chemoresista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 68 publications
(91 reference statements)
0
1
0
Order By: Relevance
“…This is not in line with literature reporting sLe X to be mainly regulated by FUT6 in CRC as well as breast cancer ( 27 , 77 ). Interestingly, in AML cell lines, we found that (s)Le A/X antigen expression was positively correlated with FUT7 instead of FUT3/4 ( 78 ). We hypothesize that the biosynthesis of glycans might be regulated by different GTs in a disease- and tissue-specific manner.…”
Section: Discussionmentioning
confidence: 77%
“…This is not in line with literature reporting sLe X to be mainly regulated by FUT6 in CRC as well as breast cancer ( 27 , 77 ). Interestingly, in AML cell lines, we found that (s)Le A/X antigen expression was positively correlated with FUT7 instead of FUT3/4 ( 78 ). We hypothesize that the biosynthesis of glycans might be regulated by different GTs in a disease- and tissue-specific manner.…”
Section: Discussionmentioning
confidence: 77%